Circular chemistry: Adapting linear chemistry to mitigate the climate crisis - Bianca Stadelmann; Chris Slootweg (Mètode Science Studies Journal: Annual Review)
In this article we explore the imperative shift from a linear economic model to a circular one, with a particular focus on the pivotal role of chemistry in this transition. It elucidates the critical global challenges stemming from unsustainable resource extraction and the linear «take-make-dispose» approach, including climate change, resource depletion, and biodiversity loss. Circular chemistry emerges as a promising solution, guided by principles of green chemistry and circular economy. It advocates for perpetual material cycles, emphasizing sustainable end-of-life strategies and product design that prioritizes reuse and recycling. We underscore the need for chemistry to prioritize efficiency, safety, and circularity, while also addressing challenges associated with complex waste streams and the responsible mineralization of chemicals. Achieving circular chemistry necessitates cooperation among individuals, educational and scientific institutions, industries, and regulatory bodies, and as such it can significantly contribute to mitigating global environmental crises by establishing sustainable material circulation as a cornerstone principle.